2020
DOI: 10.1016/j.scitotenv.2020.139631
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater surveillance for population-wide Covid-19: The present and future

Abstract: Wastewater-based epidemiology (WBE) could play critical roles in the Covid-19 pandemic. • WBE can help solve the pressing problem of insufficient clinical diagnostic testing. • It could serve to better target and direct the application of diagnostic testing. • It could help reduce countless domino effects from the pandemic. • WBE might be the only means for providing rapid, inexpensive mass surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
290
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(296 citation statements)
references
References 57 publications
4
290
0
2
Order By: Relevance
“…A study from Australia ( Ahmed et al, 2020 ) showed that the number of infected individuals in the catchment areas could be reasonably estimated by detecting the copy numbers of SARS-CoV-2 RNA in the wastewater, which verified that early detection of coronavirus in wastewater might be a viable surveillance strategy for COVID-19 infections ( Daughton, 2020 ; Orive et al, 2020 ; Wu et al, 2020b ) as previously demonstrated for hepatitis A virus, norovirus ( Hellmér et al, 2014 ) and poliovirus ( Asghar et al, 2014 ; Lodder et al, 2012 ). Although there was no sufficient evidence that fecal-oral transmission of COVID-19 was viable, while there was evidence showed that SARS-CoV-2 could be easily and sustainably transmitted in the community in Shenzhen, China, because the proportion of COVID-19 patients without definite exposure from January 25 through February 5 (11%) was much higher than that before January 24 (6%) ( Liu et al, 2020 ).…”
Section: Resultssupporting
confidence: 61%
“…A study from Australia ( Ahmed et al, 2020 ) showed that the number of infected individuals in the catchment areas could be reasonably estimated by detecting the copy numbers of SARS-CoV-2 RNA in the wastewater, which verified that early detection of coronavirus in wastewater might be a viable surveillance strategy for COVID-19 infections ( Daughton, 2020 ; Orive et al, 2020 ; Wu et al, 2020b ) as previously demonstrated for hepatitis A virus, norovirus ( Hellmér et al, 2014 ) and poliovirus ( Asghar et al, 2014 ; Lodder et al, 2012 ). Although there was no sufficient evidence that fecal-oral transmission of COVID-19 was viable, while there was evidence showed that SARS-CoV-2 could be easily and sustainably transmitted in the community in Shenzhen, China, because the proportion of COVID-19 patients without definite exposure from January 25 through February 5 (11%) was much higher than that before January 24 (6%) ( Liu et al, 2020 ).…”
Section: Resultssupporting
confidence: 61%
“…Given the trends in COVID-19 case load with the SARS-CoV-2 RNA abundance in wastewater there are several potential applications for using SARS-CoV-2 RNA wastewater data to inform public health interventions 45…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that more than half (55%) of those tested for fecal viral RNAs were positive and noted that the virus is excreted in the feces for long periods, and in some cases, beyond negative testing or with respiratory symptoms 13 . Wastewater-Based Epidemiology (WBE) is an epidemiological tool improve predictions and assist in mitigating COVID-19 outbreaks by evaluating biomarkers in a speci c community 14 . The primary advantage is related to minimizing domino effects such as unnecessarily long stay-at-home policies that stress humans and economies alike 15 .…”
Section: Introductionmentioning
confidence: 99%